2021
DOI: 10.14710/mkts.v26i2.30762
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of regulations on fly ash as a hazardous waste in Indonesia and several countries

Abstract: This paper aims to encourage the Indonesian government to review the 2014 Government Regulation (PP) number 101 related to coal-ash. Fly ashes at power plants overload the landfills and requires complete handling solution. The utilization of fly ash in Indonesia are facing the issues, one of these is the categorization of fly ash as a hazardous waste. As a result, its utilization requires permissions from the ministry of environment and forestry. In this paper, a comparative study of fly ash classification as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…Third, based on comparative studies conducted in various parts of the world, it was found that countries that had issued FABA waste as B3 waste. Countries such as the United States, China, Vietnam, and India gave fly ash and bottom ash (FABA) as toxic waste and two industrial wastes (Ekaputri & Bari, 2021). In line with Więckowski1 and 2019) emphasized that even if the fly ash has been removed from B3 waste, it still harms the environment.…”
Section: Methodsmentioning
confidence: 99%
“…Third, based on comparative studies conducted in various parts of the world, it was found that countries that had issued FABA waste as B3 waste. Countries such as the United States, China, Vietnam, and India gave fly ash and bottom ash (FABA) as toxic waste and two industrial wastes (Ekaputri & Bari, 2021). In line with Więckowski1 and 2019) emphasized that even if the fly ash has been removed from B3 waste, it still harms the environment.…”
Section: Methodsmentioning
confidence: 99%
“…Abu layang yang dihasilkan dari proses pembakaran batubara di Indonesia mencapai 15.027.100 ton pada tahun 2019. Akan tetapi, pemanfaatan abu layang di Indonesia masih rendah yaitu 10-12% tiap tahun (Triwulan dkk., 2017;Ekaputri dan Bari, 2020). Abu layang yang telah dimanfaatkan di Indonesia sebanyak 73% berasal dari pulau Jawa dan pemanfaatan dari pulau lain masih dibawah 30%.…”
Section: Pendahuluanunclassified
“…Sehingga penghasil FABA tidak lagi harus mengurus pelaporan dan perizinan dalam pengelolaannya [1]. Salah satu yang mendasari adanya regulasi tersebut adalah fakta bahwa hingga tahun 2020 saat FABA masih ditetapkan sebagai limbah B3 dan pemanfatannya membutuhkan perizinan dari KLHK, jumlah limbah fly ash yang dimanfaatkan di Indonesia sejumlah 10-12% dengan sejumlah 73% diolah di pulau jawa, dan sisanya di luar pulau jawa [4]. Akibatnya, PLTU akan mengalami pembengkakan biaya operasional sehingga secara tidak langsung akan meningkatkan tarif dasar listrik.…”
Section: Pendahuluanunclassified